Effectiveness of Online vs Offline classes for EFL Classroom : a study case in a higher education. - NURUL RACHMAH (Universitas Lambung Mangkurat, 2020)
With the increasing development of technology, online teaching is more readily accepted as a viable component in teaching and learning. Online and Offline class, particularly in developing countries, in its early stages and not without its challenges. This study exposed 16 EFL students of university Ibnu Khaldun responses to an online classroom and offline classroom. And investigates common student perceptions of the online lesson as compared with offline lessons to identify the effectivness between online and offline class. The method use data analysis adopted from questionnaires using qualitative (Likert scale questions) and quantitative (open-ended questions) approaches provided data for content analysis to determine common student perception. The result, more students associated in-class lessons. They felt more interest, due to better understanding, classroom interaction with the lecturer and student, and enjoy during the lesson. The student prefer to the offline larning than online learning. Keyword : Online class, Offline class and English Foreign Language (EFL)